Design, Synthesis and Characterization of a Visible‐Light‐Sensitive Molecular Switch and Its PEGylation Towards a Self‐Assembling Molecule. Issue 50 (13th July 2022) - Paolino, Marco; Saletti, Mario; Reale, Annalisa; Licciardi, Mariano; Varvarà, Paola; Marquette, Arnaud; Léonard, Jérémie; Bonechi, Claudia; Donati, Alessandro; Giorgi, Gianluca; Giuliani, Germano; Carlotti, Benedetta; et al.
Abstract: HBDI‐like chromophores represent a novel set of biomimetic switches mimicking the fluorophore of the green fluorescent protein that are currently studied with the hope to expand the molecular switch/motor toolbox. However, until now members capable of absorbing visible light in their neutral (i. e. non‐anionic) form have not been reported. In this contribution we report the preparation of an HBDI‐like chromophore based on a 3‐phenylbenzofulvene scaffold capable of absorbing blue light and photoisomerizing on the picosecond timescale. More specifically, we show that double‐bond photoisomerization occurs in both the E ‐to‐ Z and Z ‐to‐ E directions and that these can be controlled by irradiating with blue and UV light, respectively. Finally, as a preliminary applicative result, we report the incorporation of the chromophore in an amphiphilic molecule and demonstrate the formation of a visible‐light‐sensitive nanoaggregated state in water. Abstract : Exploiting the conjugation of the 3‐phenyl benzofulvene scaffold, we prepared a new HBDI‐like chromophore capable of absorbing blue light and photoisomerizing in the picosecond timescale. The PEGylation of this photoswitch lead to a visible light‐sensitive amphiphilic molecule capable of self‐assembly in water to give a spherical nanoaggregated structure.